ANALISIS FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA BANK PERKREDITAN RAKYAT DI KOTA PEKANBARU (PERIODE TAHUN 2012 SAMPAI DENGAN TAHUN 2016) - Aziri, Rahmat Dian; Kamaliah, Kamaliah; Savitri, Enni (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to Analyze the Influence of Capital Adequacy Ratio(CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), OperationalCost and Operating Income (BOPO) to Return On Assets (ROA). Then to Test andAnalyze Influence of the most dominant variable in influencing Return On Assets(ROA).The data used is the publication of the Annual Report of Bank Indonesiafrom 2012 to 2016 sampling technique used was purposive sampling criteria ruralbanks (BPR) which has been operating in Pekanbaru during the period ofobservation the years 2012 until 2016 and submitted to Bank Indonesia. Obtaineda sample of 18 company number rural banks (BPR) which has been operating inPekanbaru during the observation period 2012 until 2016. The hypothesis wastested using t-statistics to test the significance of the partial regressioncoefficients and F-statistics to test the significance of regression coefficientstogether -sama at the 5% level of significance.The result of research there are influence of Capital Adequacy Ratio(CAR) and Operational Cost of Operating Income (BOPO) to Return On Assets(ROA). While the Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL)does not affect the Return On Assets (ROA) of the Rural Banks (BPR). Fromdeterminant coefficient test (Adj R2) it is known that the Capital Adequacy Ratio(CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) andOperational Income Operating (BOPO) variables only succeeded in influencingReturn On Assets (ROA) amounted to 13.60%, meaning there is another 86.40%influenced by other variables.